Unmet Healthcare Needs and Related Factors Among Immigrants: A Cross-Sectional Secondary Analysis of 2019 Korea Community Health Survey Data - SookKyoung Park PhD; Hye Young Kim PhD; Young-Me Lee PhD (SAGE Publishing, 2023)
Immigrants in Korea face numerous difficulties in seeking medical services due to language and cultural differences. Providing medical services to them could be beyond the institutional capacity of the host country owing to factors such as, physical and psychological problems, social unrest, language barriers, and problems adapting to unfamiliar environments. According to Andersen's health service use behavioral model, we used a multifaceted approach to explore the factors influencing the unmet healthcare needs of immigrants in Korea from the Korean health system. This cross-sectional secondary analysis study used data from the 2019 Korea Community Health Survey of 3524 immigrants. Their unmet healthcare needs were calculated using a complex, weighted sample design. Group differences in categorical variables were analyzed using the Rao-Scott chi-square test. Logistic regression analysis was used to analyze the association between unmet healthcare needs and ageing factors. Overall, 262 (7.4%) of surveyed immigrants experienced unmet healthcare needs. Factors influencing unmet healthcare needs were being a woman (OR = 1.41, 95% CI = 1.03-1.94), national primary livelihood security receiver (OR = 1.44, 95% CI = 1.29-1.68), stress (OR = 1.34, 95% CI = 1.26-1.45), perceived health status (poor: OR = 2.35, 95% CI = 1.58-3.52), and perceived health status (moderate: OR = 1.62, 95% CI = 1.18-2.20). Policymakers could focus on these predictors when formulating policy strategies to reduce unmet health care needs. In addition, by effectively delivering services that meet the unmet healthcare needs of immigrants, their right to health is protected.